Group 'em together
a
b
−
a
+
1
−
b
a
b
−
a
=
a
(
b
−
1
)
Notice that there will be a 1 as without it it'll simply be ab
1
−
b
=
1
(
1
−
b
)
Notice that it doesn't match with the upper one... so we'll change the signs
1
(
1
−
b
)
=
−
1
(
b−
1
)
(try to multiply them now!!
Jot them down in one expression
a
(
b
−
1
)
−
1
(
b
−
1
)
You get!!!!!!
(
a
−
1
)
(
b
−
1
)
Answer:
10 I think
Step-by-step explanation:
well we add it all together 2+1+3+4
Answer:
255
Step-by-step explanation:
total cost paid = fixed cost + total variable cost
total variable cost = distance travelled x variable cost per unit
two equations can be derived from the question
a + 10b = 105 equation 1
a + 15b = 155 equation 2
a = fixed cost
b = variable cost per unit
Subtract equation 1 from 2
5b = 50
b = 10
Substitute for b in equation 1
a + 10(10) = 105
a = 105 - 100 = 5
a = 5
cost of travelling a distance of 25km
5 + 10(25) = 255
Answer:
Step-by-step explanation:
Answer:
4 miles
Step-by-step explanation: